MARKETING AN INTRODUCTION - MASTERSON ROSALIND; NICHOLA PHILIPS; DAVID PICKTON (NEW DELHI SAGE PUBLICATION INDIA PVT LTD, 2021)
A foundational text for aspiring marketers, "Marketing: An Introduction" by Rosalind Masterson, often co-authored in later editions with Nichola Phillips and David Pickton, offers a clear and accessible gateway into the dynamic world of marketing. The book is widely recognized for its practical approach, effectively bridging marketing theory with real-world applications through a wealth of case studies, examples, and pedagogical features. Aimed primarily at undergraduate students, it provides a thorough grounding in the core principles and contemporary practices of the field.
MARKETING
MANAGEMENT
BBA & MBA
Keywords: MARKETING; MANAGEMENT